PENGEMBANGAN BAHAN AJAR FLIPBOOK MATERI SENI RUPA PADA MATA PELAJARAN SENI BUDAYA DAN PRAKARYA DI SEKOLAH DASAR - Istiyati Mahmudah; Laura Kalaij Javanoca; Fatma Wardah (Al-Mudarris: Journal Of Education, 2026)
The purpose of this research was to develop digital flipbook teaching materials for third-grade students at SDN 6 Palangka Raya. The flipbooks were designed using the Canva application and then published through the Heyzine platform for digital access. This research employed a Research and Development (R&D) approach with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation.The results showed that the developed flipbook teaching materials achieved a very high level of validity, with an average design validation score of 92.5 and a material validation score of 91. Implementation of the teaching materials, involving 28 students, demonstrated significant improvements in learning outcomes, with an average pretest score of 84.4 and a posttest score of 93. Furthermore, student and teacher responses to the teaching materials were categorized as very excellent. Based on these results, it can be concluded that flipbook-based teaching materials can be an innovative alternative for digital learning. This study is expected to provide references for the development of more engaging and interactive teaching materials in the future.